Salivary Lipid Peroxidation and Total Sialic Acid Levels in Smokers and Smokeless Tobacco Users as Maraş Powder - Naciye Kurtul; Engin Gökpınar (Mediators of Inflammation)
Maraş powder (MP), a different type of smokeless tobacco (ST) and prepared from a tobacco of species Nicotiana rustica Linn, is widely used in Turkey. We aimed to investigate the effects of MP on salivary total sialic acid (TSA) and malondialdehyde (MDA) levels and to compare these parameters in smokers and MP users (MPUs). The salivary TSA and MDA concentrations were significantly higher in the smokers and MPU than those of control subjects and also in MPU than that of smokers. We have also observed that as the number of cigarettes consumed and MP amount increases, TSA and MDA levels increase too. In smokers, MDA values were significantly correlated with the number of cigarettes smoked and the duration of smoking. In MPU, both MDA and TSA levels were significantly correlated with the duration of MP use and the amount of daily consumed MP. We have concluded increased salivary TSA and MDA levels associated in MPU and smokers. Results can help to evaluate harmful effects of these habits. It is important to point out that bigger change in the measured parameters has been observed for MP use. This observation may be an important indication of harmful effects of ST use as MP.